Handbook of Face Recognition - Li, Stan Z.; Li, Stan Z.; Jain, Anil K.; Jain, Anil K. (Springer New York : Imprint: Springer, 2005)
Increased interest in face recognition stems from rising public concern for safety, the need for identity verification in the digital world, and the need for face analysis and modeling techniques in multimedia data management and computer entertainment. This authoritative handbook is the first to provide complete coverage of face recognition, including major established approaches, algorithms, systems, databases, evaluation methods, and applications. After a thorough introductory chapter from the editors, 15 chapters address the sub-areas and major components necessary for designing operational face recognition systems. Each chapter focuses on a specific topic, reviewing background information, reviewing up-to-date techniques, presenting results, and offering challenges and future directions. Features & Benefits: *Provides comprehensive coverage of the main concepts, including face detection, tracking, alignment, feature extraction, and recognition *Presents state-of-the-art methods and algorithms for designing face image-processing and recognition systems *Examines design of secure, accurate, and reliable face recognition systems *Describes performance evaluation methods and major applications, such as security, person verification, Internet communication, and computer entertainment *Integrates numerous supporting graphs, tables, charts, and performance data This accessible, practical reference is an essential resource for scientists and engineers, practitioners, government officials, and students planning to work in image processing, computer vision, biometrics and security, Internet communications, computer graphics, animation, and the computer game industry. Stan Z. Li leads research programs in face detection and recognition, biometrics, and surveillance at Microsoft and is a senior member of the IEEE. Anil K. Jain is university-distinguished professor in the department of computer science and engineering at Michigan State University, as well as a fellow of the ACM, IEEE, and IAPR. Key Topics: Face detection, tracking, and alignment Performance evaluation Subspace analysis methods Illumination and pose modeling Morphable models of faces Facial skin-color modeling Face expression analysis and synthesis Psychological and neural perspectives -- Security / Pattern Recognition -- Intermediate / Advanced.